UNVEILING THE DYNAMICS OF DOMESTIC PRICES OF CACAO BEANS IN INDONESIA - Olivia Kristianti Kusuma; Jessica; Yohan Chandrasukmana; Ferry Vincenttius Ferdinand (Ikatan Dosen Menulis, 2024)
This study is crucial for understanding the factors affecting cacao bean prices in Indonesia. Cacao is a vital commodity in the country's economy, and fluctuations in its price impact various stakeholders. By analyzing these factors, we can make informed decisions benefiting the government, industry, and cacao farmers. The purpose of this study is to analyze the domestic price of cacao beans in Indonesia. The dependent variable in this study is the domestic price of cacao in Indonesia, while the independent variables are volume of cacao bean exports, volume of cacao bean imports, global price of cacao beans, volume of domestic production of cacao beans, Rupiah to USD exchange rate, the federal reserve rate, Gross Domestic Product (GDP) annual growth rate of Indonesia, and export duties imposed on export of cacao beans. This research design utilizes time series data from 1996 to 2022 to analyze the factors influencing the domestic price of cacao beans in Indonesia. The results of the analysis show that the variables of the volume of cacao bean imports, the global price of cacao beans, Rupiah to USD exchange rate, and dummy variable for export duties imposed on export of cacao beans are significant affecting the domestic price of cacao. While volume of cacao bean exports, the federal reserve rate, volume of domestic production of cacao beans and GDP annual growth rate of Indonesia are not significant. The non-significance of volume of cacao bean exports, the federal reserve rate, volume of domestic production of cacao beans, and GDP annual growth rate could be caused by weak relationships, multicollinearity, data issues, or model specification limitations.